Bioabsorbable metal screws in traumatology: A promising innovation. (April 2017) - Biber, Roland; Pauser, Johannes; Brem, Matthias; Bail, Hermann Josef
Abstract: MAGNEZIX® CS (Syntellix AG, Hanover, Germany) is a bioabsorbable compression screw made of a magnesium alloy (MgYREZr). Currently there are only two clinical studies reporting on a limited number of elective patients who received this screw in a hallux valgus operation. We applied MAGNEZIX® CS for fixation of distal fibular fracture in a trauma patient who had sustained a bimalleolar fracture type AO 44-B2.3. Clinical course was uneventful, fracture healing occurred within three months. Follow-up X-rays showed a radiolucent area around the implant for some months, yet this radiolucent area had disappeared in the 17-months follow-up X-ray.